Disain dan Implementasi Inverter Satu Fasa Dengan Output Sinusoidal Menggunakan Metode Modulasi SPWM - effendi effendi; Intan Nurul Fajri (J-Innovation, 2022)
Single-phase inverter with sinusoidal output in this research was arranged by using Arduino Uno that aim as pulse wave generator, where the ON and OFF pulse times are obtained by using the SPWM (Sinusoidal Pulse Width Modulation) modulation method. This modulation compare a sinusoidal reference wave that has frequency 50 Hz with a carrier wave in form of triangular with a frequency of 2 KHz. To get the time of each pulse, formerly a simulation is carried out using a computer (PSIM Program), furthermore by using the programming language on Arduino this pulse wave is used to trigger the H-Bridge circuit which is composed of components in the form of MOSFETs by using with help four TLP 250 circuits. The output wave from the H-Bridge circuit futhermore connected to a filter circuit that consist of inductor and capacitor components to get the output in the form of a sinusoidal wave at a resistive load of 44 Ohms.